Effect of North American Ginseng on 137Cs-induced Micronuclei in Human Lymphocytes - Lee, Tung-Kwang; Wang, Weidong; O'Brien, Kevin F.; Roberta, Johnke; Allison, Ron R.; Diaz, Angelica; Wang, Tao (East Carolina University, 2008)
To explore the radioprotective effect of a standardized North American ginseng extract (NAGE) on human peripheral blood lymphocytes (PBL), a micronuclei (MN) assay was conducted in PBL obtained from 12 volunteers. NAGE (50â 1000 Âµg/mL) and WR-1065 (1 mm and 3 mm) were applied to PBL cultures at 0 h and 90 min post-irradiation. It was found that (1) the baseline MN yield of PBL ranged from 14.4 Â± 1.5 to 15.9 Â± 1.5 per 1000 binucleated cells (p > 0.05); after irradiation (1 Gy and 2 Gy), the MN yield increased sharply; (2) MN yields declined with increasing concentrations of NAGE and WR-1065. Even at 90 min post-irradiation of 1 Gy, the maximum level of MN reduction rate caused by NAGE and WR-1065 was 53.8% and 59.2%, respectively; after 2 Gy irradiation, it was 37.3% and 42%, respectively; (3) the MN distribution in PBL followed a non-Poisson distribution in all cases; and (4) both NAGE and WR-1065 showed no significant effect on the proliferation index of lymphocytes. The results indicate that NAGE is a relatively non-toxic natural product, which can be administered as a dietary supplement and has the potential to be a radiation countermeasure. Originally published Phytotherapy Research Vol. 22, No. 12 2008.
Keywords: Ginseng; WR-1065; Radioprotection; Micronuclei; Lymphocytes